THE ROLE OF THE COMMUNITY IN SUPPORTING THE MANAGEMENT OF LEANG-LEANG AS A TOURIST ATTRACTION IN MAROS REGENCY - Naila Nabila; Andi Fatimah Maoudy A Bakty (Politeknik Pariwisata Makassar, 2025)
This study aims to analyze the level of community participation in the management of Leang-leang and propose efforts to optimize community participation in Leang-leang. This study applies a qualitative method conducted in Leang-Leang, Maros Regency, during the period of September-October 2025, through field observations, in-depth interviews with the surrounding community, and supported by literature studies. The results of the study show that the community plays an important role in three main aspects: (1) environmental and prehistoric site preservation, through cleanliness activities, monitoring potential vandalism, and passing on knowledge about the cultural values of Leang-Leang to the younger generation; (2) local economic development, by utilizing business opportunities such as tour guides, providing local cuisine, and selling handicrafts with a prehistoric cultural nuance; and (3) collaboration with the government and management, especially in developing tourism infrastructure, improving service quality, and conservation education programs for tourists. To that end, optimization measures are needed in the form of capacity building through training, the formation of tourism awareness groups (Pokdarwis) oriented towards conservation, and the strengthening of collaboration between the government, site managers, academics, and local communities. These recommendations are expected to encourage more sustainable, community-based management of Leang-Leang while preserving its inherent cultural values. However, this study also found challenges, namely limited human resource capacity, a lack of tourism training, and suboptimal distribution of economic benefits to all levels of society. Therefore, a strategy is needed to strengthen community participation through community-based training programs, creative economic empowerment, and increasing tourist awareness of the importance of preserving the sustainability of prehistoric sites. In conclusion, the management of Leang-Leang cannot rely solely on the government or formal management, but must place the community as the main actor in creating sustainable tourism. This study's recommendations emphasize the need for multi-stakeholder collaboration based on community-based tourism (CBT) so that Leang-Leang remains preserved as a world cultural heritage while providing tangible benefits for the welfare of the local community.